Optimal margin distance of bullectomy for primary spontaneous pneumothorax reduces postoperative recurrence - Tsuboshima, Kenji; Matoba, Yasumi; Wakahara, Teppei (Journal of Thoracic Disease, 2019)
Background: For primary spontaneous pneumothorax, bullectomy using autosutures is the standard procedure. Despite performing various methods for preventing postoperative recurrence, it remains relatively high. Although considering the margin distance of bullectomy is important, no argument has been discussed for the optical margin distance until now. Hence, we evaluated the optimal margin distance for bullectomy of spontaneous pneumothorax, bullectomy to reduce postoperative recurrence. Methods: Between March 2015 and May 2018, 91 eligible candidates from 142 cases, who underwent video-assisted thoracoscopic bullectomy for spontaneous pneumothorax, bullectomy, were evaluated. We analysed the factors preventing postoperative recurrence, including the margin distance using the inverse- probability of treatment weighted method by propensity score was used to adjust for heterogeneous patient backgrounds. Results: The patients’ median age was 20 years (range, 14–86 years). Postoperative recurrences occurred in 8 cases (8.8%). The margin distance was 9.1±5.0 mm. The cut-off point of the margin distance was defined as 5.0 mm. The inverse-probability of treatment weighted method indicated that a margin distance ≥5.0 mm significantly prevented postoperative recurrence (P=0.0076, hazard ratio =0.18). Conclusions: This study suggests that a margin distance of ≥5.0 mm for bullectomy of PSP can reduce postoperative recurrence.